Validity and Reliability of Basic Life Support Intention Questionnaire for Nurses at Dr. Soebandi Hospital Jember - Baskoro Setioputro; Amanda Rizky Amanda Rizky; Wantiyah (KHD Production, 2023)
Based On the Theory of Planned Behaviour perspective, basic life support intention is determined by attitudes, perception of a social norm, perceived self-efficacy, and control ability in performing basic life support. This study analyzed the validity and reliability of the basic life support intention questionnaire, designed to measure basic life support intention among nurses. A total of 48 items were developed based on literature reviews encompassing four main constructs: attitude, social norms, self-efficacy, and control ability. The questionnaire then underwent a validation process, including construct and content validity (CVI) and reliability analysis. This study was conducted on nurses in Dr. Soebandi Hospital Jember. The questionnaire was distributed to 160 nurses, of whom only 80 questionnaires were returned. The results of the CVI test on 36 questionnaire statements found that the CVI value was in the range 0,85-1. In comparison, the results of the construct validity test on 48 questionnaire statements were found to be valid and obtained 21 statement items. Reliability test-retest results obtained a coefficient correlation value of 0,75 and an alpha value of 0,669, which means it is reliable. The final set of basic life support intentions consisted of 21 items measuring attitude (four items), social norms (seven items), self-efficacy (six items), and control ability (four items) of practicing basic life support intention. The basic life support intention questionnaire was shown to be valid and reliable.